Analysis of color change and translucency of glass ionomer cements, a key material for older adults restorations - Andrade, Carolina Alves; Rocha, Letícia Marinho Silva; Santos, Eric Mayer dos; Shimokawa, Carlos Alberto Kenji; Sobral, Maria Ângela Pita (Brazilian Dental Science, 2025)
Objective: This study evaluated color change (deltaE00) and translucency (TP) of GICs over 3 months. Materials and Methods: Discs (n = 5) of conventional (ION-Z [IZ], Maxxion R [MX], Vidrion R [VR], Riva Self Cure [RSC], GC Gold Label 9 [G9] and resin-modified GICs (GC Gold Label 2 [G2], Equia Forte [EF]) were prepared and stored in distilled water. Color measurements were taken (3x/disc) with a reflectance spectrophotometer at 5 experimental times: immediately after preparation; after 1 hour (1h), 1 day (1d), 1 week (1w), and 3 months (3m). Data were analyzed using two-way repeated-measures ANOVA/Tukey test (alpha=0.05) Results: After 3 months, all GICs presented perceptible deltaE00, with MX and RSC exhibiting the highest values. EF consistently showed acceptable deltaE00 MX and RSC showed the highest TP after 1h and throughout (p<0.05). G2, RSC, G9, and VR showed their highest TP values at 1w and 3m, with no differences between these times (p - > 0.05). IZ showed the highest TP at 1d and 1w, and EF’s greatest TP was at 3m. Conclusion: GICs showed perceptible color changes with unstable translucency. EF maintained acceptable color change. KEYWORDS Color; Dental care for aged; Dental restoration failure; Glass ionomer cements; Colorimetry.